Bearing capacity of interbedded weak sedimentary rock / Kamaruzzaman Mohamed - Mohamed, Kamaruzzaman (2010)
Strength and behavior of shallow foundation on rock have been based on uniaxial compressive strength of intact rock sample in which is formulated as the bearing capacity of rock mass. Literature studies showed that the empirical correlations of bearing capacity of the rock mass were developed from a single type and isotropic rock. This research work is to assess and determine the bearing capacity and behavior of shallow footing on anisotropic and heterogeneous rock mass such as interbedded Kenny Hill formation, its established state as sedimentar y weak rock, its constitutions of weathered sandstone and shale.